DYSFUNCTIONAL HIGH DENSITY LIPOPROTEINS IN TYPE 2 DIABETES - Ismoilov, Jamshid Abduraimovich; Egamberdiyeva, Yulduz Komiljon kizi; Mahmamuradova , Nargiza Negmatullayevna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
The risk of developing cardiovascular diseases (CVD) in people with type 2 diabetes mellitus (T2DM) increases by 2–4 times. One of the major factors increasing cardiovascular risk is dyslipidemia, which involves abnormalities in all lipoproteins, including high-density lipoprotein (HDL). The development of T2DM is accompanied not only by a decrease in HDL levels, but also by significant changes in their structure. This leads to the transformation of native HDL into so-called dysfunctional, or diabetic, HDL, which lose their antiatherogenic, cardioprotective, anti-inflammatory and antidiabetic properties. In poorly controlled diabetes, HDL can not only lose its beneficial functions, but also acquire pro-atherogenic and pro-inflammatory functions. Diabetic HDL may contribute to the development of adverse processes such as increased proliferation, migration and invasion of cancer cells. Considering that HDL, in addition to participating in cholesterol transport, perform important regulatory functions in the body, there is reason to assume that structural modifications of HDL (oxidation, glycation, enrichment with triglycerides, loss of HDL-associated enzymes, etc.) are one of the reasons for the development of vascular complications diabetes